Bone marrow mesenchymal stem cell–derived exosomal miR‐206 promotes osteoblast proliferation and differentiation in osteoarthritis by reducing Elf3. Issue 16 (23rd June 2021) - Huang, Yijiang; Zhang, Xiumeng; Zhan, Jingdi; Yan, Zijiang; Chen, Daosen; Xue, Xinghe; Pan, Xiaoyun
Abstract: MicroRNAs (miRNAs) serve as gene silencers involved in essential cell functions. The role of miR‐206 and E74‐like factor 3 (Elf3) has been identified in osteoarthritis (OA), while the effect of exosomal miR‐206 from bone marrow mesenchymal stem cells (BMSCs) in OA remains largely unknown. Thus, we aim to explore the role of exosomal miR‐206 from BMSCs in OA with the involvement of Elf3. BMSCs and BMSC‐derived exosomes (BMSC‐exos) were obtained and identified. OA mouse models were constructed by anterior cruciate ligament transection and then treated with BMSC‐exos or BMSC‐exos containing miR‐206 mimic/inhibitor. The expression of miR‐206, Elf3, inflammatory factors, osteocalcin (OCN) and bone morphogenetic protein 2 (BMP2) in mouse femoral tissues was assessed. The pathological changes in mouse femur tissues were observed. The mouse osteoblasts were identified and treated with untransfected or transfected BMSC‐exos, and then, the expression of miR‐206, Elf3, OCN and BMP2 was determined. The alkaline phosphatase (ALP) activity, calcium deposition level, OCN secretion, proliferation, apoptosis and cell cycle arrest in osteoblasts were measured. MiR‐206 was down‐regulated while Elf3 was up‐regulated in OA animal and cellular models. Exosomal miR‐206 ameliorated inflammation and increased expression of OCN and BMP2 in mouse femoral tissues. Moreover, exosomal miR‐206 promoted ALP activity, calcium deposition level, OCN secretion and proliferation and inhibited apoptosis in OA osteoblasts. Overexpressed Elf3 reversed miR‐206 up‐regulation‐induced effects on OA osteoblasts. BMSC‐derived exosomal miR‐206 promotes proliferation and differentiation of osteoblasts in OA by reducing Elf3. Our research may provide novel targets for OA treatment.